Solve for y -8*(-6y)=6

Math
-8⋅(-6y)=6
Multiply -6 by -8.
48⋅y=6
Divide each term by 48 and simplify.
Tap for more steps…
Divide each term in 48⋅y=6 by 48.
48⋅y48=648
Cancel the common factor of 48.
Tap for more steps…
Cancel the common factor.
48⋅y48=648
Divide y by 1.
y=648
y=648
Cancel the common factor of 6 and 48.
Tap for more steps…
Factor 6 out of 6.
y=6(1)48
Cancel the common factors.
Tap for more steps…
Factor 6 out of 48.
y=6⋅16⋅8
Cancel the common factor.
y=6⋅16⋅8
Rewrite the expression.
y=18
y=18
y=18
y=18
The result can be shown in multiple forms.
Exact Form:
y=18
Decimal Form:
y=0.125
Solve for y -8*(-6y)=6

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top